Reattachment of Coronal Fragment Using Fiber-Reinforced Post: A Case Report - ZORBA, Yahya Orcun; ÖZCAN, Erdal (European Journal of Dentistry, 2007)
Coronal fractures of permanent dentition are the most frequent type of dental injury. If the original tooth fragment is retained following fracture, the natural tooth structures can be reattached using adhesive protocols. The development and use of fiber-reinforced composite root canal posts make possible of the reattachment of the crown esthetically. This case report presents a clinical technique to reattachment maxillary lateral incisor tooth after trauma using direct fiber-reinforced post systems. At the 1-year follow-up, a slightly marginal discoloration, but no recurrent decay or composite clefts were detected and the resultant appearance was acceptable to the patient. (Eur J Dent 2007;1:174-178)
Keywords: Reattachment; Trauma; Fiber-reinforced post